2017
DOI: 10.1186/s12883-017-0959-2
|View full text |Cite
|
Sign up to set email alerts
|

A novel frameshift GRN mutation results in frontotemporal lobar degeneration with a distinct clinical phenotype in two siblings: case report and literature review

Abstract: BackgroundProgranulin gene (GRN) mutations are major causes of frontotemporal lobar degeneration. To date, 68 pathogenic GRN mutations have been identified. However, very few of these mutations have been reported in Asians. Moreover, some GRN mutations manifest with familial phenotypic heterogeneity. Here, we present a novel GRN mutation resulting in frontotemporal lobar degeneration with a distinct clinical phenotype, and we review reports of GRN mutations associated with familial phenotypic heterogeneity.Cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…GRN mutations are rare in Asian cohorts and absent in Korea and Hong Kong [16][17][18][19][20][21]. Four GRN mutations were reportedly associated with positive family history of FTLD: the first was in 2 Chinese sisters with CBS [22], then a Japanese female individual with primary progressive aphasia and mother with dementia [17], a patient with bvFTD from South India [18], and a Japanese with primary progressive aphasia whose brother had CBS [23]. They would be category 2-3 by Goldman's criteria [6].…”
Section: Discussionmentioning
confidence: 99%
“…GRN mutations are rare in Asian cohorts and absent in Korea and Hong Kong [16][17][18][19][20][21]. Four GRN mutations were reportedly associated with positive family history of FTLD: the first was in 2 Chinese sisters with CBS [22], then a Japanese female individual with primary progressive aphasia and mother with dementia [17], a patient with bvFTD from South India [18], and a Japanese with primary progressive aphasia whose brother had CBS [23]. They would be category 2-3 by Goldman's criteria [6].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, whilst cases have been reported, MAPT 52,53 and GRN mutations remain less prevalent amongst Asian compared to Western cohorts 50,55,56 . A South Korean study found 2 novel missense variants of unknown significance in both MAPT and GRN in 2% of patients but did not identify any pathogenic variants 15 .…”
Section: Discussionmentioning
confidence: 92%
“…47 Similarly, whilst cases have been reported, MAPT 52,53 and GRN mutations remain less prevalent amongst Asian compared to Western cohorts. 50,55,56 A South Korean study found 2 novel missense variants of unknown significance in both MAPT and GRN in 2% of patients but did not identify any pathogenic variants. 15 In our cohort, four pathogenic/likely pathogenic mutations in GRN were observed in 3 nfvPPA/indeterminant PPA and 1 bvFTD; one VUS in nfvPPA/indeterminant PPA.…”
Section: Discussionmentioning
confidence: 99%
“…The GRN A9D missense mutation disrupts the signal sequence of the progranulin peptide, thus preventing both its lysosomal localization and secretion into the extracellular space [44,[46][47][48]. Other missense and splice site mutations cause frameshifts or large genomic deletions that result in aberrant protein products ultimately destined for ER-associated degradation [49,50]. Two pathogenic cysteine mutations, C521Y and C139R, do not cause progranulin haploinsufficiency but abolish progranulin's neurotrophic effects in vitro and may impact progranulin's proteolytic cleavage, which is necessary for production of functional granulins [51].…”
Section: Frontotemporal Dementiamentioning
confidence: 99%